Basaloid squamous carcinoma of the oral cavity. Report of a case - de Araújo, Vera Cavalcanti; Biazolla, Eder Ricardo; Moraes, Norberto Perri; Furuse, Takeo Adhemar; Melhado, Ronaldo Maia (Elsevier, 1993)
A case of basaloid squamous carcinoma that involves the posterior buccal mucosa is described. The major histopathologic feature is a carcinoma with a basaloid pattern in association with squamous differentiation. The basaloid cells exhibit large and vesicular nuclei and eosinophilic clear or vacuolated cytoplasm. Cells are distributed in cords, trabeculae, or lobules that occasionally show glandular arrangement. The majority of the tumor cells are positive for keratin and a large group of cells distributed in glandular arrangement are positive also for vimentin. © 1993.